ANALISIS STRATEGI MENARIK MINAT KONSUMEN KERAK TELOR DALAM MASA PANDEMI - Yulianti, Aulia (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
ABSTRACT The research was conducted to see the business strategies applied by Micro, Small and Medium Enterprises (MSMEs) in the face of the Covid-19 pandemic. The object of research is a typical Betawi food industry with a culinary characteristic of egg crust which is located on Jalan Setu Babakan which is located in South Jakarta or around Monas. The method used is a qualitative research method with a descriptive approach. Based on the research results, it was obtained data that the business strategy in marketing its products is through social media. From the results of the research above, it can be explained that this strategy can work as expected by paying attention to the purchasing power of consumers during the Covid-19 pandemic. However, by using social media facilities, the funds needed by small business actors have an impact on reducing business capital. From the description above, it can be rejected, that the role of the government and banking is very important, especially with regard to training in the use of information technology so that small business products can survive amid the Covid-19 pandemic.